The influence of the accession negotiations between the EU and Turkey on Turkey's employment and social policies - Göksel Kuşlu (Europa-Kolleg Hamburg, Institute for European Integration, 2015)
This paper aims to look into the effects of the accession negotiations between the EU and Turkey on Turkey's employment and social policies and attempts to assess the level of compliance of the Turkish legislation with the EU Acquis in this field. As a candidate country, Turkey is required to transpose and implement the EU Acquis on employment and social policy, which constitutes the 19th chapter in the EUTurkey negotiation process. This sine qua non condition for the accession provided a catalyst for legislative and institutional reforms with regards to employment rights, social dialogue, health and safety at work, gender equality and non-discrimination. It was found that Turkish legislation is in compliance or mostly complies circa 70% of the EU Directives in employment and social policy field. The analysis based on indicators also revealed that Turkey lagged far behind its European counterparts exactly in those social and employment policy areas where the highest compliance deficits were observed.
Keywords: 320; Turkey-EU relations; accession negotiations; EU acquis; employment and social policy; employment and social indicators